Impact of cryopreservation on viability, gene expression and function of enteric nervous system derived neurospheres - Heumüller, Sabine; Maurer, Kristina; Tapia-Laliena, María Angeles; Sticht, Carsten; Christmann, Anne; Mörz, Handan; Khasanov, Rasul; Wink, Elvira; Schulte, Steven; Greffrath, Wolfgang; Treede, Rolf-Detlef; Wessel, Lucas; et al. (Frontiers in cell and developmental biology, 2023)
Introduction: Impairment of both the central and peripheral nervous system is a major cause of mortality and disability. It varies from an affection of the brain to various types of enteric dysganglionosis. Congenital enteric dysganglionosis is characterized by the local absence of intrinsic innervation due to deficits in either migration, proliferation or differentiation of neural stem cells. Despite surgery, children’s quality of life is reduced. Neural stem cell transplantation seems a promising therapeutic approach, requiring huge amounts of cells and multiple approaches to fully colonize the diseased areas completely. A combination of successful expansion and storage of neural stem cells is needed until a sufficient amount of cells is generated. This must be combined with suitable cell transplantation strategies, that cover all the area affected. Cryopreservation provides the possibility to store cells for long time, unfortunately with side effects, i.e., upon vitality.Methods: In this study we investigate the impact of different freezing and thawing protocols (M1-M4) upon enteric neural stem cell survival, protein and gene expression, and cell function.Results: Freezing enteric nervous system derived neurospheres (ENSdN) following slow-freezing protocols (M1-3) resulted in higher survival rates than flash-freezing (M4). RNA expression profiles were least affected by freezing protocols M1/2, whereas the protein expression of ENSdN remained unchanged after treatment with protocol M1 only. Cells treated with the most promising freezing protocol (M1, slow freezing in fetal calf serum plus 10% DMSO) were subsequently investigated using single-cell calcium imaging. Freezing of ENSdN did not alter the increase in intracellular calcium in response to a specific set of stimuli. Single cells could be assigned to functional subgroups according to response patterns and a significant shift towards cells responding to nicotine was observed after freezing.Discussion: The results demonstrate that cryopreservation of ENSdN is possible with reduced viability, only slight changes in protein/gene expression patterns and without an impact on the neuronal function of different enteric nervous system cell subtypes, with the exception of a subtle upregulation of cells expressing nicotinergic acetylcholine receptors. In summary, cryopreservation presents a good method to store sufficient amounts of enteric neural stem cells without neuronal impairment, in order to enable subsequent transplantation of cells into compromised tissues.